Development of Thai Reading and Writing Spells Using Skill Exercises of Thai Language Learning Subject Group Grade 1 Students at Pratuchai School Phra Nakhon Si Ayutthaya Province - Lakul, Anan; Rummabut, Haruetai (Dhammathas Academic Journal, 2023)
The research objectives were: 1) to compare reading and spelling abilities of the 1st grade students before and after learning management by using the exercises and 2) to study the opinions of grade 1 students towards learning management by using the exercises. The sample group used in this research were Pratuchai school grade 1 students Phra Nakhon Si Ayutthaya province the first semester of the academic year 2022 by selecting 1 classroom, namely Prathom 1/7 students, there are 36 students. The tool used is learning management plan according to the skill training model It is a tool used for organizing learning activities, teaching reading and writing spelling. Grade 1 and the statistics used were percentage (%), mean (x̅), t-test (T-Test), and standard deviation (S.D.). The research findings indicate that: 1. The ability of reading and spelling writing skills of the 1st grade students after learning by using the exercises was higher with statistically significant at the level of 0.05. 2. Opinions of Prathomsuksa 1 students towards learning management by using skills exercises overall, the opinions were moderate.